Let‐7 regulates radial migration of new‐born neurons through positive regulation of autophagy. (23rd March 2017) - Petri, Rebecca; Pircs, Karolina; Jönsson, Marie E; Åkerblom, Malin; Brattås, Per Ludvik; Klussendorf, Thies; Jakobsson, Johan
Abstract: During adult neurogenesis, newly formed olfactory bulb (OB) interneurons migrate radially to integrate into specific layers of the OB. Despite the importance of this process, the intracellular mechanisms that regulate radial migration remain poorly understood. Here, we find that microRNA (miRNA) let‐7 regulates radial migration by modulating autophagy in new‐born neurons. Using Argonaute2 immunoprecipitation, we performed global profiling of miRNAs in adult‐born OB neurons and identified let‐7 as a highly abundant miRNA family. Knockdown of let‐7 in migrating neuroblasts prevented radial migration and led to an immature morphology of newly formed interneurons. This phenotype was accompanied by a decrease in autophagic activity. Overexpression of Beclin‐1 or TFEB in new‐born neurons lacking let‐7 resulted in re‐activation of autophagy and restored radial migration. Thus, these results reveal a miRNA‐dependent link between autophagy and adult neurogenesis with implications for neurodegenerative diseases where these processes are impaired. Synopsis: The highly expressed let‐7 family is crucial for radial migration of adult new‐born neurons in the olfactory bulb. The molecular mechanisms underlying this process include the positive regulation of neuronal autophagy. let‐7 is highly expressed in new‐born olfactory bulb neurons. Knockdown of let‐7 impairs radial migration. let‐7 acts through positive regulation of autophagy. Activation of autophagy restores let‐7‐impaired migration. Abstract : Adult neurogenesis requires interneurons to migrate and integrate in the olfactory bulb in a process that depends on let‐7‐dependent control of autophagy.